Enhanced sensitivity of guided mode resonance sensor through super-mode excitation at near cut-off diffraction. (December 2020) - Deb, Hironmay; Srisuai, Nantarat; Jolivot, Romuald; Promptmas, Chamras; Mohammed, Waleed S.; Boonruang, Sakookan
Highlights: Super-mode resonance in 2D GMR sensor at near cut-off was demonstrated. 2D-GMR having Ta2 O5 film coated on 2D imprinted grating on glass was fabricated. Modal allocation is performed using an approximated four-layer waveguide and RCWA. Resonance sensitivity more than two-fold enhancement is measured. Abstract: This work theoretically and experimentally demonstrates sensitivity enhancement in dielectric guided mode resonance (GMR) sensor via controlling a super-mode resonance at nearly cut-off diffraction (or at Rayleigh wavelength.) A bulk refractive index sensitivity can reach the upper limit at the value linearly proportional to the grating's periodicity. Super-mode excitation in the multilayer configuration of the 2D GMR sensor (a high refractive index film coated on a low refractive index imprinted grating) is demonstrated. This concept is verified using numerical calculations: Rigorous Coupled Wave Analysis (RCWA) and Homogeneous Waveguide Approximation (HWA). Modal allocation for each resonance in the GMR structure is performed using the approximated four-layer waveguide. The measured super-mode resonance has shown sensitivity enhancement almost three folds of that of the traditional guide mode resonance. Also, this realization occurs in a broad dynamic range through optimization of the structure's parameters. This guarantees a usage in multiple sensing applications.